2013
DOI: 10.1042/an20130037
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelation and Multiple Sclerosis

Abstract: Histochemical and MRI studies have demonstrated that MS (multiple sclerosis) patients have abnormal deposition of iron in both gray and white matter structures. Data is emerging indicating that this iron could partake in pathogenesis by various mechanisms, e.g., promoting the production of reactive oxygen species and enhancing the production of proinflammatory cytokines. Iron chelation therapy could be a viable strategy to block iron-related pathological events or it can confer cellular protection by stabilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 222 publications
(392 reference statements)
0
39
0
2
Order By: Relevance
“…Data concerning animal and human studies show that DFO has diverse neuroprotective effects and its use is beneficial in Huntington’s [5,6], Alzheimer’s [7,8], Parkinson’s [911] disease, amyotrophic lateral sclerosis [12], prionopathies [13], neuroferritinopathy [14], intracerebral hemorrhage [3,15], ischemic stroke [16,17], multiple sclerosis [18], and spinal cord injury [19]. Unfortunately, most of these studies used forms of systemic administration or intracranial injections that are not suitable for human use [9].…”
Section: Introductionmentioning
confidence: 99%
“…Data concerning animal and human studies show that DFO has diverse neuroprotective effects and its use is beneficial in Huntington’s [5,6], Alzheimer’s [7,8], Parkinson’s [911] disease, amyotrophic lateral sclerosis [12], prionopathies [13], neuroferritinopathy [14], intracerebral hemorrhage [3,15], ischemic stroke [16,17], multiple sclerosis [18], and spinal cord injury [19]. Unfortunately, most of these studies used forms of systemic administration or intracranial injections that are not suitable for human use [9].…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, perivascular inflammation may damage vessel walls, leading to blood extravasation with subsequent perivascular iron deposition. [29][30][31][32] While iron thus accumulates within the basal ganglia, the opposite occurs within the thalamus. We found a decrease of R2* relaxation rates during follow-up in CIS and even more pronounced in MS.…”
mentioning
confidence: 96%
“…Histochemical studies revealed iron deposits around MS plaques, 11,27,28 indicating that iron could originate from damaged brain structures. One may further speculate that iron is subsequently redistributed within the brain, 29,30 where in particular deep gray matter structures could serve as a sink. 5 In addition, perivascular inflammation may damage vessel walls, leading to blood extravasation with subsequent perivascular iron deposition.…”
mentioning
confidence: 98%
“…Several studies showed that chelators ameliorate experimental autoimmune encephalomyelitis which is an animal model of MS. These promising results triggered interest in examining iron removal therapy in MS patients [169][170][171].…”
Section: Multiple Sclerosismentioning
confidence: 99%